Muslim societies in the age of mass consumption politics, culture and identity between the local and the global - Pink, Johanna (Cambridge Scholars, 2009)
In the course of the 20th century, hardly a region in the world has escaped the triumph of global consumerism. Muslim societies are no exception. Globalized brands are pervasive, and the landscapes of consumption are changing at a breathtaking pace. Yet Muslim consumers are not passive victims of the homogenizing forces of globalization. They actively appropriate and adapt the new commodities and spaces of consumption to their own needs and integrate them into their culture. Simultaneously, this culture is reshaped and reinvented to comply with the mechanisms of conspicuous consumption. It is these processes that this volume seeks to address from an interdisciplinary perspective. The papers in this anthology present innovative approaches to a wide range of issues that have, so far, barely received scholarly attention. The topics range from the changing spaces of consumption to Islamic branding, from the marketing of religious music to the consumption patterns of Muslim minority groups. This anthology uses consumption as a prism through which to view, and better understand, the enormous transformations that Muslim societies-Middle Eastern, South-East Asian, as well as diasporic ones-have undergone in the past few decades.